The road to dissidence of Pera Todorović - Radović Danijel B. (Baština)
Pera Todorović (1852-1907) is one of the most intriguing figures in the political life of Serbia in the second half of the 19th and the beginning of the 20th century. He is one of the main ideologues of Serbian radicalism, and has had a tremendous influence on the work and organization of the People's Radical Party. In addition, he distinguished himself as an influential journalist and a good writer. The paper analyzes his political activity after his release from prison in January 1886, which was preceded by an agreement with King Milan Obrenović. The agreement with the ruler freed his political comrades from prison and enabled the Radical Party to resume its political activities. However, the radicals were not satisfied with Todorovic's policies and his commitment to make an agreement with the Progressive Party. His and the policy of the Main Board of the party increasingly diverged, and Todorović very quickly became a dissident and a bitter opponent of the radicals.